Transaction Cost Analysis of Sustainable Management of Terubuk Fish (Tenualosa macrura) in the Waters of Bengkalis Riau - Deni Efizon; Bintal Amin; Dessy Yoswaty; Trisla Warningsih; Alit Hindri Yani; Herimufty Herimufty; Gatot Yulianto; Deviasari Deviasari; Rival Junaidi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
This research was conducted in a terubuk fishermen area in Bengkalis District (3 villages), Bukit Batu District (4 villages) in Bengkalis Regency; Sungai Apit District (2 villages), Siak Regency and Tasik Putri Puyu District (2 villages) in Meranti Islands Regency. The location is densely populated by fishermen with the largest fishery reserve in the waters of Bengkalis, Riau. This study was carried out to examine the transaction costs in the management of terubuk fish in Bengkalis waters. A survey was administered to collect primary data and secondary data through interview and focus group discussions with stakeholders relevant to Terubuk fisheries reserves (fishermen and the government). The transaction cost structure of terubuk fish management was determined using transaction cost analysis. Analytical method using the equation . The results of the study showed that the total transaction costs required in the management of terubuk fish in Bengkalis waters reported by the government reached IDR 1,505,134,000 for a year. Meanwhile, the transaction cost of fishermen was IDR 95,750,000 per year which is significantly lower than the one reported by the government. The cost included the decision-making costs, information costs, and joint operational cost.